Estudo das propriedades estruturais do ácido mefenâmico complexado a série de lantanídeos - Royo, Fernanda Morera (2016)
Organic molecules, when combined with a metal, can create efficient electronic devices that serve a new nanoscale market, the OLEDs. In this work, we chose the mefenamic acid, widely used in the pharmaceutical industry until then, as an organic molecule to be complexed with the metals of the lanthanide series, elements that have spectroscopic and magnetic properties, investigating their structural changes for each element of the series, aiming at Its future application in modern electronic devices. For this, we will use Raman Spectroscopy, a non-invasive technique of applying intense monochromatic light beam on a sample to analyze the result of the interaction, observing its similarities and divergences graphically.